2002
DOI: 10.1126/science.1073616
|View full text |Cite
|
Sign up to set email alerts
|

Maps of Subsurface Hydrogen from the High Energy Neutron Detector, Mars Odyssey

Abstract: After 55 days of mapping by the High Energy Neutron Detector onboard Mars Odyssey, we found deficits of high-energy neutrons in the southern highlands and northern lowlands of Mars. These deficits indicate that hydrogen is concentrated in the subsurface. Modeling suggests that water ice-rich layers that are tens of centimeters in thickness provide one possible fit to the data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
211
1
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 357 publications
(228 citation statements)
references
References 11 publications
15
211
1
1
Order By: Relevance
“…No clear relationship between polygon dimension and ground-ice content, which increases with latitude (e.g., Feldman et al, 2004), could be observed on Mars (Mangold et al, 2004;Mangold, 2005;Levy et al, 2009a). The size of the upland polygons (UP1) is consistent with the findings of the Gamma Ray Spectrometer (GRS) that only~4 tõ 10 wt.% water-ice equivalent exists currently in the upper surface layer (b1 m depth) in the regions between 45°S and 45°N Mitrofanov et al, 2002;Feldman et al, 2004). If higher ground-ice contents than in the upper layer occur deeper than 1 m, which was inferred from the dimension of the scalloped depressions (Morgenstern et al, 2007;Ulrich et al, 2010), seasonal thermal waves should not reach this depth at the present time (Mellon, 1997;Mangold et al, 2004).…”
Section: Genesis Of Mars Polygons and Environmental Implicationssupporting
confidence: 64%
“…No clear relationship between polygon dimension and ground-ice content, which increases with latitude (e.g., Feldman et al, 2004), could be observed on Mars (Mangold et al, 2004;Mangold, 2005;Levy et al, 2009a). The size of the upland polygons (UP1) is consistent with the findings of the Gamma Ray Spectrometer (GRS) that only~4 tõ 10 wt.% water-ice equivalent exists currently in the upper surface layer (b1 m depth) in the regions between 45°S and 45°N Mitrofanov et al, 2002;Feldman et al, 2004). If higher ground-ice contents than in the upper layer occur deeper than 1 m, which was inferred from the dimension of the scalloped depressions (Morgenstern et al, 2007;Ulrich et al, 2010), seasonal thermal waves should not reach this depth at the present time (Mellon, 1997;Mangold et al, 2004).…”
Section: Genesis Of Mars Polygons and Environmental Implicationssupporting
confidence: 64%
“…However, the presence of water ice in the shallow subsurface midlatitude and polar regions Mitrofanov et al 2002;Byrne et al 2009), along with the detection of perchlorates in polar and equatorial soil Glavin et al 2013;Ming et al 2014) and of chloride-bearing deposits in the southern highlands at low and midlatitudes (Osterloo et al 2008), is important because they can melt this ice at Mars' present-day environmental conditions and produce liquid saline water (brine) (Clark 1978;Brass 1980;Clark and Van Hart 1981;Haberle et al 2001;Chevrier and Altheide 2008;Rennó et al 2009;McEwen et al 2011;Ojha et al 2015).…”
Section: Liquid Water and The H 2 O Cyclementioning
confidence: 99%
“…In 2002, GRS data, which are directly dependent on the concentrations of hydrogen, and therefore almost certainly upon the concentration of water, within roughly one meter of the surface, showed the presence of extensive ground ice within this upper meter above $50°latitude in both hemispheres (Feldman et al, 2002;Boynton et al, 2002;Mitrofanov et al, 2002); concentrations typically range from $2 to 5 wt% at $40°l atitude to $20 wt% at 60°latitude, generally increasing polewards . Ice-stability models, which are consistent with the GRS observations, show that ground ice within a meter, or less, of the surface should generally be stable above 45-55°lat-itude (e.g., Mellon and Jakosky, 1993;Allen and Kanner, 2007).…”
Section: Introductionmentioning
confidence: 99%